Topological Structure of Urban Street Networks from the Perspective of Degree Correlations. (October 2014) - Jiang, Bin; Duan, Yingying; Lu, Feng; Yang, Tinghong; Zhao, Jing
Many complex networks demonstrate a phenomenon of striking degree correlations: that is, a node tends to link to other nodes with similar (or dissimilar) degrees. From the perspective of degree correlations, in this paper we attempt to characterize topological structures of urban street networks. We adopted six urban street networks (three European and three North American), and converted them into network topologies in which nodes and edges represent individual streets and street intersections, respectively, and compared the network topologies with three reference network topologies (biological, technological, and social). The urban street network topologies (with the exception of Manhattan) showed a consistent pattern that distinctly differs from the three reference networks. The topologies of urban street networks lack striking degree correlations in general. Through reshuffling the network topologies towards, for example, maximum or minimum degree correlations while retaining the initial degree distributions, we found that all the surrogate topologies of the urban street networks, as well as the reference ones, tended to deviate from small-world properties. This implies that the initial degree correlations do not have any positive or negative effect on the networks' performance or functions.